Heme as Possible Contributing Factor in the Evolvement of Shiga-Toxin Escherichia coli Induced Hemolytic-Uremic Syndrome - Wijnsma, Kioa L.; Veissi, Susan T.; de Wijs, Sem; van der Velden, Thea; Volokhina, Elena B.; Wagener, Frank A. D. T. G.; van de Kar, Nicole. C. A. J.; van den Heuvel, L. P. (Frontiers in Immunology, 2020)
Shiga-toxin (Stx)-producing Escherichia coli hemolytic-uremic syndrome (STEC-HUS) is one of the most common causes of acute kidney injury in children. Stx-mediated endothelial injury initiates the cascade leading to thrombotic microangiopathy (TMA) , still the exact pathogenesis remains elusive. Interestingly, there is wide variability in clinical presentation and outcome. One explanation for this could be the enhancement of TMA through other factors. We hypothesize that heme, as released during extensive hemolysis, contributes to the etiology of TMA. Plasma levels of heme and its scavenger hemopexin and degrading enzyme heme- oxygenase- 1 (HO-1) were measured in 48 STEC-HUS patients. Subsequently, the effect of these disease-specific heme concentrations, in combination with Stx, was assessed on primary human glomerular microvascular endothelial cells (HGMVECs).Significantly elevated plasma heme levels up to 21.2 µM were found in STEC-HUS patients compared to controls and were inversely correlated with low or depleted plasma hemopexin levels (R2 -0.74). Plasma levels of HO-1 are significantly elevated compared to controls. Interestingly, especially patients with high heme levels (n=12, heme levels above 75 quartile range) had high plasma HO-1 levels with median of 332.5 (86-720) ng/mL (p=0.008).Furthermore, heme is internalized leading to a significant increase in reactive oxygen species production and stimulated both nuclear translocation of NF-κB and increased levels of its target gene (tissue factor).In conclusion, we are the first to show elevated heme levels in patients with STEC-HUS. These increased heme levels mediate endothelial injury by promoting oxidative stress and a pro-inflammatory and pro-thrombotic state. Hence, heme may be a contributing and driving factor in the pathogenesis of STEC-HUS and could potentially amplify the cascade leading to TMA.